Objects on the Web : - Ben-Natan, Ron (McGraw-Hill, 1997)
A complete guide to using objects in Web and client/server environments, this book describes the technology and solutions provided by the convergence of the two major computing trends of the decade: the Web and objects. Here the author explains how to build and deploy object-oriented Web applications, covering such technologies as WebObjects, ActiveX, Java, and many others.